Kolase terhadap Kemampuan Motorik Halus Anak Cerebral Palsy - Dila, Fifi Ratna; Sugihartatik, Sugihartatik; Udhiyanasari, Khusna Yulinda (JOEAI (Journal of Education and Instruction), 2025)
This study aimed to determine the effect of collage activities on the fine motor skills of fourth-grade children with spastic cerebral palsy at Patrang Special Needs School (SLBN). The method employed was Single-Subject Research (SSR) with an A-B design. The results showed an increase in fine motor skills in the intervention phase compared to the baseline phase, with a final score reaching 91.6%. This study demonstrates that collage activities utilizing the cutting and pasting technique with corn kernels have a positive impact on the fine motor development of children with cerebral palsy. In conclusion, these findings suggest that collage-based art activities can serve as an alternative learning medium and therapeutic tool to enhance fine motor skills in children with special needs. In conclusion, collage activities have a positive effect on the fine motor skills of fourth-grade children with spastic cerebral palsy at Patrang Special Needs School.   Keywords: Cerebral Palsy, Collage, Fine Motor Skills, Single Subject Research